Fluoride inhibition of oxygen consumption and increased oxidative stress in rats - Fina, Brenda Lorena (2012)
The aim of this work was to evaluate the effect of fluoride (F) on oxygen consumption (VO2) in rats and how it might affect the respiratory chain and the levels of reactive oxygen species (ROS). Eighteen Sprague-Dawley rats were divided into three groups: Control, NaF20, and NaF40,which received 0, 20, and 40 µmol F/100 g bw/day for 30 days, respectively. In vivo, VO2 decreased 90 min after treatment with F, whereas TBARS, CAT, and GPx were higher. In vitro, F decreased VO2in liver and in mitochondria. These results support the hypothesis that the bone inflammatory foci observed in treatments with NaF could involve an inhibition of the respiratory chain that would cause increase in reactive oxygen species (ROS).